PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PENGANGKUTAN KAYU TANPA DOKUMEN SAH DI WILAYAH HUTAN TAMAN NASIONAL BUKIT TIGA PULUH KABUPATEN TEBO - Cindo Kottama; Sigit Somadiyono; Fatriansyah Fatriansyah (Universitas Batanghari Jambi, 2021)
Marriage is an inner and outer bond between men and women that is entwined in a domestic relationship to create a household that is sakinah mawaddah warahmah. One of the condotiont that must be obeyed in the implementation of a marriage regulated by law is that the bride and groom must be of legal age. Every marriage that has not meet the marriage age limit, is essentially called a underage marriage is affirmed in article 7 of law Number 1 of 1974 and article 1 paragraph (1) of Law Number 23 of 2002 Concerning Child Protecdtion, that is child someone who is not yet 18 years old and is a pruning of the freedom of chldren’s rights in obtaining the rights to life as a teenager who has the potential to grow, develop and potentially positively according to what is outlined in religion. The problems discussed in this thesis are the intercourse of minors in marital relations and the effects arising from such marriages, because in fiqih view no punishman is given for this action. However, if viewed from the perspective of national law, underage marriages have violated several law and regulations. The factors that influence it’s effectiveness are the subtance of the law Article 332 of the Criminal Code, Law Number 16 of 2019 and Law Number 23 of 2002. The conclusion of this thesis is that the aplication of sanctions against underage run away women in marriage in Tanjung Jabung Timur Regency has never been applied because the are no reports from the victims althought the criminal law regulates sanctions againts the perpetrators because it has caused harm to the victims (women).